The Practitioner's Bookshelf: In Praise of the Human Rights Textbook. (8th August 2020) - Phillips, Brian
Abstract: This instalment of 'The Practitioner's Bookshelf' makes the case for the human rights textbook as an appealing option for human rights practitioners needing to refresh and extend their knowledge and understanding of recent developments in our field. The author assesses a quartet of new human rights textbooks with particular reference to their discussion of contemporary thinking and debate among scholars and practitioners about the definition of torture in international law.